Optimization of Manufacturing Parameters Affecting on Characterization of Porous Sintered Tin-Bronze Alloy - Al-Ethari, Haydar; H. Haleem, Ali; I. Ali, Osamah (International Journal of Engineering and Technology, 2018)
Porous sintered bronze alloy has widespread applications in various engineering fields such as filtration systems, self-lubricating bearings, fluid flow control, heat exchanger ..etc. In this paper, powder metallurgy technique using NaCl particles high purity (99.5%) as a space holder (pore-forming agent) was employed to produce a rigid porous structure . The paper aimed at studying Â and identifying the effect of manufacturing parameters (NaCl wt. %, compacting Â pressure, sintering temperature and sintering duration) on the characteristics of porous tin-bronze alloy . AccordingÂ toÂ Response Surface MethodologyÂ analysis a multi-optimizationÂ methodÂ based onÂ desirability function used to obtain the optimum process conditions that can be used inÂ manufacturingÂ ofÂ porous sintered tin-bronze structure. These optimum conditions were: (35.36 wt.%NaCl), (40 MPa) compacting pressure , sintering temperature of (193.5 oC) and sintering time of (180 min)Â to get maximum porosity of (66.32 %) , permeability coefficient of (2.96*10-3 cm/min.) and micro-hardness of (57.12 Hv).Â Â